Review Paper: Monitoring Steel Bridges With Natural Frequency: Inggris - Priyo Novendri Darimolyo; Guntur Nugroho; Ahmad Zaki (Jurnal Perspektif, 2026)
Dynamic load analysis is a method for monitoring the health of bridge structures, particularly those made of steel, used to ensure safety and comfort. This analysis yields natural frequencies, which are the frequencies at which an object vibrates when subjected to free vibration. Structural failure due to dynamic loads, caused by resonance when the external frequency aligns with the natural frequency, underscores the importance of bridge structural health monitoring. Extensive research has been conducted on natural frequencies in steel bridge structures, and research mapping using bibliometric and scientometric methods can help analyze research gaps. Bibliometric analysis methods include document trends, publication type, country of origin and document productivity, as well as publication relevance and impact. Scientometric analysis uses VOS Viewer to map and analyze research collaborations. This study aims to describe the relationship between publications, keywords, and trends in crack monitoring studies in concrete structures over the past decade (2015–2025). Data collection from Scopus revealed 54 related documents during that period. Bibliometric and scientometric analyses were used to explore publication trends, collaborations between authors and countries, and the distribution of document types, which showed a sharp increase in publications in 2022. China topped the list in terms of the number of publications, followed by the United States, Belgium, and Italy. This analysis demonstrated the dominance of scientific articles as a document type, highlighting the need for broader international collaboration to further develop steel bridge health monitoring systems and more advanced technologies. The study emphasizes the importance of improving structural health monitoring, particularly regarding the influence of natural frequencies, which remains understudied.